ANALISIS VALUE FOR MONEY DALAM PENGUKURAN KINERJA KEUANGAN PEMERINTAHAN DESA KECAMATAN TAMBANG KABUPATEN KAMPAR PERIODE 2021-2023 - Mardlotillah, Utami; Putri, Annie Mustika; Suriyanti, Linda Hetri (Jurnal Akuntansi Kompetif, 2025)
This study analyzes the financial performance of village governments in Tambang District, Kampar Regency, from 2021 to 2023, using the "Value for Money" concept. The research employs a mixed-methods approach, beginning with a quantitative analysis of Village Revenue and Expenditure Budget (APBDes) realization reports from 17 villages, followed by in-depth qualitative interviews with village heads and financial officers to explain the quantitative findings. The results indicate that most villages demonstrate outstanding economic performance and very satisfactory effectiveness in revenue management, often exceeding targets. However, efficiency remains a significant challenge, with many villages categorized as "Less Efficient" or "Inefficient" due to spending often exceeding revenue. Key obstacles include external factors like the Covid-19 pandemic and regulatory changes and internal issues such as suboptimal project management and revenue fluctuations. The study concludes that strengthening realistic budget planning, improving project management, enhancing internal oversight, and increasing human resource capacity are crucial. This research contributes to public sector accounting by emphasizing the integration of economic efficiency and effectiveness indicators for accountable and transparent village financial governance, aligning with Stewardship Theory.